Endometrial Scratching in Australia, New Zealand and the UK: A Follow-up Survey - Sarah LENSEN; Madina SARWARI; Kiri BEILBY; Karin HAMMARBERG; Martha HICKEY (Fertility & Reproduction, 2022)
Background: Endometrial scratching is a common IVF add-on. In 2015, a survey in Australia, New Zealand and the UK reported that 83% of fertility specialists recommended endometrial scratching for IVF (1). Several large trials have since been published reporting no clear evidence for improved live birth rates following endometrial scratching before IVF. Aim: To ascertain the current practices and views on endometrial scratching across Australia, New Zealand and the UK. Method: An anonymous online survey was distributed via professional fertility societies and through emails sent directly to Medical Directors of IVF clinics in Australia, New Zealand and the UK. Responses were received between October and December 2020. Results: 121 eligible responses were received (fertility specialists (n=61), embryologists (n=26) and fertility nurses (n=24)); at least one response was received from 40% of IVF clinics. Among fertility specialists, 34% currently offer endometrial scratching, primarily in the case of recurrent implantation failure. Most respondents (>90%) were neutral or did not believe endometrial scratching improved pregnancy and live birth rates. However, for women with recurrent implantation failure, 29% believed it was beneficial. More than half (55%) of respondents viewed reducing psychological distress as a benefit of endometrial scratching. Among fertility specialists who were not offering endometrial scratching, 51% previously did. Conclusion: This study indicates the use of endometrial scratching has declined over the last five years, which may reflect a response to recent evidence reporting no benefit from the procedure. The major limitations of this study are the low response rate, and the potential for bias; professionals with strong views about endometrial scratching (for or against) may have been more likely to complete the survey.